2023
DOI: 10.3390/su15021625
|View full text |Cite
|
Sign up to set email alerts
|

GIS-Based Visitor Count Prediction and Environmental Susceptibility Zoning in Protected Areas: A Case Study in Plitvice Lakes National Park, Croatia

Abstract: The most valuable protected natural areas, including national parks, are subjected to the increased visitors count and density, threatening the environmental sustainability and biodiversity conservation. To establish a basis for land management to mitigate these influences, the novel geographic information (GIS)-based environmental susceptibility zoning method was proposed. The study area covered the Plitvice Lakes National Park, as the oldest and largest national park in Croatia, using the historical 20-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…This trend is evident in the works of García Hernández [10], Peran López [11], Kostopoulou & Kyritsis [12], López-Bonilla & López-Bonilla [13], Maggi & Fredella [14], García Hernández et al [15], Alazaizeh [16], Santos & Pena Cabrera [17], Viñals et al [18,19], Conti [20], Cruz Aragón [21], Becken & Wardle [22], Guo & Chung [23], Milano [24], and Muler González et al [25]. Over the past five years, the literature demonstrated that recreational carrying capacity continues to be a crucial tool in managing natural parks, archaeological sites, and historical centres, as highlighted in the studies of Zubiaga et al [26], Jurišić et al [27], Llausàs et al [28], Raj Sharma & Bisht [29], Bao et al [30], Red de Parques Nacionales [31], Deffinika et al [3], and Santos & Brilha [32], among others. Its application is also used in different contexts as evidenced in the study of indoor spaces by Petronijević et al [33].…”
Section: Background and State Of The Artmentioning
confidence: 99%
“…This trend is evident in the works of García Hernández [10], Peran López [11], Kostopoulou & Kyritsis [12], López-Bonilla & López-Bonilla [13], Maggi & Fredella [14], García Hernández et al [15], Alazaizeh [16], Santos & Pena Cabrera [17], Viñals et al [18,19], Conti [20], Cruz Aragón [21], Becken & Wardle [22], Guo & Chung [23], Milano [24], and Muler González et al [25]. Over the past five years, the literature demonstrated that recreational carrying capacity continues to be a crucial tool in managing natural parks, archaeological sites, and historical centres, as highlighted in the studies of Zubiaga et al [26], Jurišić et al [27], Llausàs et al [28], Raj Sharma & Bisht [29], Bao et al [30], Red de Parques Nacionales [31], Deffinika et al [3], and Santos & Brilha [32], among others. Its application is also used in different contexts as evidenced in the study of indoor spaces by Petronijević et al [33].…”
Section: Background and State Of The Artmentioning
confidence: 99%